1968
DOI: 10.1136/thx.23.6.571
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of serious complications of corticosteroid therapy in respiratory disease: A retrospective survey of patients in the Brompton Hospital

Abstract: A retrospectively controlled study is described of mortality and serious morbidity in 550 patients treated with corticosteroids and 499 controls. The overall incidence of side-effects was similar in both groups, but gastro-intestinal bleeding, diabetes, and mental disturbance early in treatment occurred more frequently in the corticosteroid group. Other individual side-effects did not occur significantly more often than in the controls, but there was an overall increased frequency of complications with increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

1981
1981
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(42 citation statements)
references
References 29 publications
4
38
0
Order By: Relevance
“…Smyllie HC et al and Slatore CG et al concluded that glucose control is more difficult with steroid based therapy in COPD. 25,27 Impaired glucose tolerance and diabetes mellitus is less common in patients taking inhaled corticosteroid therapy which is comparable to previous studies conducted by Spencer S et al and Calverley PM et al 14,15 …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Smyllie HC et al and Slatore CG et al concluded that glucose control is more difficult with steroid based therapy in COPD. 25,27 Impaired glucose tolerance and diabetes mellitus is less common in patients taking inhaled corticosteroid therapy which is comparable to previous studies conducted by Spencer S et al and Calverley PM et al 14,15 …”
Section: Discussionsupporting
confidence: 76%
“…[17][18][19][20][21][22][23][24] Glucose control is more difficult with steroid based therapy in COPD. [25][26][27] One study shows 15% of COPD patient requires additional treatment for hyperglycemia as compared to 4% of control group. [28][29][30] In addition to this some case reports describe loss of glucose control in patient receiving ICS based therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Their effects on the hypothalamic-pituitary-adrenal (HPA) axis, immunity, glucose metabolism, growth in children, cataract development, and bone mineral density are wellestablished (16)(17)(18)(19)(20)(21)(22)(23)(24). Several studies have also reported oral/parenteral-induced adverse psychiatric effects (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). These include mood disturbances, psychosis, confusion, and memory problems.…”
Section: Corticosteroids In Asthma: Side Effects and Psychiatric Sympmentioning
confidence: 96%
“…23 Persons with silicosis, leukemia or lymphoma, end-stage renal disease treated with dialysis, or prolonged corticosteroid therapy may benefit greatly from preventive therapy if the relative risk of developing disease during their lifetimes is high, as shown in some studies [51][52][53][54][55][56][57]69,70,77,79 but not in others. 58,71,72,75,76,78 This analysis also leads to 4 additional significant conclusions about screening and preventive therapy. First, the benefits of screening are reduced if persons with positive tests do not initiate preventive therapy.…”
Section: Commentmentioning
confidence: 99%